Characterization and demonstration of a black carbon aerosol mimic for instrument evaluation. Issue 11 (2nd November 2019) - Zangmeister, Christopher D.; Grimes, Courtney D.; Dickerson, Russell R.; Radney, James G.
Abstract: This study describes the characterization of a H2 O-dispersible, highly-absorbing carbonaceous nanomaterial that mimics the morphological and spectroscopic properties of aged black carbon aerosol (BC). When atomized from aqueous suspension, the material forms particles with a collapsed morphology resembling aged soot or BC. The material is >90 percent elemental carbon and has a mass absorption coefficient ( MAC ) and spectral dependence consistent with BC values published in the literature. The MAC at a wavelength of 532 nm decreased monotonically from 8.5 to 5.8 m 2 g −1 for aerosol with mobility diameters between 150 nm to 500 nm. The single scatter albedo (SSA) at wavelengths of 405 nm and 660 nm was a function of both wavelength and mobility diameter and increased from 0.1 to 0.4 with mobility diameters between 150 nm to 400 nm. The Ångström absorption exponent ( AAE ) between λ = 405 nm and 780 nm decreased monotonically from 1.4 to 0.6 for aerosol with mobility diameters between 150 nm to 400 nm. We demonstrate that this material can be used for fast, efficient calibration of aerosol photoacoustic spectrometers and for evaluation of spectroscopic-based measurements of aerosol mass concentration using in-situ photoacoustic spectroscopy (PAS) and filter-based light attenuation measurements for up 50 µg m −3, enabling inter-method and inter-laboratory instrument comparison. Copyright © 2019 American Association for Aerosol Research